A Unique Mitochondrial Gene Block Inversion in Antarctic Trematomin Fishes: A Cautionary Tale. (3rd June 2022) - Patel, Selina; Evans, Clive W; Stuckey, Alex; Matzke, Nicholas J; Millar, Craig D
Abstract: Many Antarctic notothenioid fishes have major rearrangements in their mitochondrial (mt) genomes. Here, we report the complete mt genomes of 3 trematomin notothenioids: the bald notothen ( Trematomus ( Pagothenia ) borchgrevinki ), the spotted notothen ( T. nicolai ), and the emerald notothen ( T. bernacchii ). The 3 mt genomes were sequenced using next-generation Illumina technology, and the assemblies verified by Sanger sequencing. When compared with the canonical mt gene order of the Antarctic silverfish ( Pleuragramma antarctica ), we found a large gene inversion in the 3 trematomin mt genomes that included tRNA Ile, ND1, tRNA Leu2, 16S, tRNA Val, 12S, tRNA Phe, and the control region. The trematomin mt genomes contained 3 intergenic spacers, which are thought to be the remnants of previous gene and control region duplications. All control regions included the characteristic conserved regulatory sequence motifs. Although short-read next-generation DNA sequencing technology has allowed the rapid and cost-effective sequencing of a large number of complete mt genomes, it is essential in all cases to verify the assembly in order to prevent the publication and use of erroneous data.